Long-Term Quality of Life After Surgical Resection for Non-Small Cell Lung Cancer: The Role of Sublobar Resection - Ana María Gómez-Martínez; Alba Santo Tomás; Joaquín Calatayud; Pedro de la Calle; Elena Fernández; Carlos Alfredo Fraile; Florentino Hernando; Jose Ramón Jarabo; Luis Alfonso Arráez-Aybar (Sci, 2025)
Introduction: Surgical resection is the most effective therapy for patients with early non-small cell lung cancer (NSCLC). Impact on quality of life (QoL) includes a period until return to work, perioperative complications and development of physical sequelae. Lobectomy is the standard procedure. However, sublobar resections have shown similar oncological outcomes preserving healthy parenchyma. We analyze if sublobar resection is associated wiht less deterioration of QoL. Methods: We performed a retrospective analysis of patients undergoing surgical resection for NSCLC between 2017 and 2019. Cases were classified according to type of resection (sublobar vs lobectomies, bilobectomies and pneumonectomies). A survey with questions related to outcomes and QoL and occupational issues was performed. Results: A total of 169 answered the survey and were followed for 36 months. Segmentectomy was performed in 69 patients (40.9%). Lobectomy was the main type of resection (56.2%). Fatigue during walking was less common in patients undergoing sublobar resections (55.1% vs 72.7%; p = 0.02). No other differences were detected in temrs of QoL between both groups. Changes in familiar relationship after surgery were higher in patients under 70 years old. Most patients had not resume their work activities at the time of consultation. Conclusion: Feeling of fatigue while walking was lower in patients undergoing sublobar resections. Changes in familiar relationship were higher in younger patients. QoL was similar in both groups.